KOMUNIKASI INTERPERSONAL SEBAGAI STRATEGI DAKWAH RASULULLAH (PERSPEKTIF PSIKOLOGI) - Sakdiah, Halimatus (UIN Antasari Banjarmasin, 2016)
This paper describes about the psychological perspective on interpersonal communication as one of the strategies the Prophet in preaching. Interpersonal communication is communication btween two or more people in order to achieve the desired objectives. In the context of the history of dakwah of Rasullullah SAW, interpersonal communication has been used as a dakwah strategy of the first when he was newly appointed as an apostle and called on the Islamic religion commanded. Interpersonal communication is done by Rasullullah in psychology perspective is a communication in psychological level. Psychologically interpersonal communication will go well if the two sides are communicating it had known each other, giving each other the attention, support, openness and trust. So the use of appropriate interpersonal communication and effective will affect the success of dakwah Islamiyah.Tulisan ini memaparkan tentang perspektif psikologi tentang komunikasi interpersonal sebagai salah satu strategi Rasulullah dalam berdakwah. Komunikasi interpersonal merupakan komunikasi yang dilakukan dua orang atau lebih dalam rangka mencapai tujuan yang diinginkan. Dalam konteks sejarah dakwah Rasullullah SAW, komunikasi interpersonal telah digunakan sebagai strategi dakwah pertama pada saat beliau baru diangkat menjadi rasul dan diperintahkan menyerukan agama Islam. Komunikasi interpersonal yang dilakukan Rasullullah dalam tinjauan psikologi merupakan komunikasi tingkat psikologis. Secara psikologis komunikasi interpersonal akan berjalan dengan baik jika kedua belah pihak yang berkomunikasi itu telah mengenal satu sama lain, saling memberikan perhatian, dukungan, keterbukaan dan kepercayaan. Sehingga penggunaan komunikasi interpersonal yang tepat dan efektif akan mempengaruhi keberhasilan dakwah Islamiyah.